Stepwise Solar Methane Reforming and Water_Splitting via Lattice Oxygen Transfer in Iron and Cerium Oxides - Srirat Chuayboon; Stphane Abanades; Sylvain Rodat (My University, 2019)
Chemical‐looping reforming of methane (CLRM) involves lattice oxygen transfer in metal oxides. This study aims to compare iron (Fe 2 O 3 ) and cerium (CeO 2 ) oxides as oxygen carrier materials for isothermal solar‐driven stepwise CH 4 reforming and H 2 O splitting. Experiments are conducted in a directly irradiated lab‐scale solar reactor heated by concentrated sunlight at 950–1150 °C. Using solar energy for process heat reduces the dependence on fossil energy resources and avoids CO 2 emissions, while converting solar energy into chemical fuels. The performance of the oxygen carrier materials is compared and evaluated by determining the amount of oxygen transferred, methane conversion, syngas yield, and thermochemical cycling stability. As a result, iron oxide reduction with methane strongly depends on temperature and displays relatively lower reaction rate than CeO 2 . The reduced iron is not completely reoxidized to Fe 3 O 4 after water‐splitting because of low thermal stability resulting in strong sintering and agglomeration, thereby decreasing syngas yield and leading to material deactivation. In contrast, ceria exhibits faster reaction rate and stable syngas yield with H 2 /CO molar ratios approaching two over repeated cycles. Stable patterns in the averaged oxygen nonstoichiometry ( δ = 0.35–0.38) demonstrate excellent thermal cycling stability. Thus, using Fe 2 O 3 oxygen carrier is not suitable for solar CLRM, but iron oxide reduction with methane can be promising for solar metallurgy aiming at producing both metallic iron and syngas.
Keywords: Cerium oxide; Chemical-Looping Combustion; Chemical Looping and Thermochemical Processes